Kinetics models for the adsorption process of cd (II) ions onto rubber (hevea brasiliensis) leaf particles / Megat Ahmad Kamal Megat Hanafiah, Haslizaidi Zakaria and Suzila Shafiei - Megat Hanafiah, Megat Ahmad Kamal; Zakaria, Haslizaidi; Shafiei, Suzila (2006)
The kinetics of Cd2+ adsorption onto Hevea Brasiliensis (HB) leaf particles were investigated at different pH using a batch adsorption technique at 30°C. Rate coefficients obtained from pseudo-second order plots were determined to range between 3.99 to 6.21 x 101 g/mg.min. The theoretical values of equilibrium adsorption capacities (qe.) also agree very well with the experimental ones. The kinetic analyses suggested that the rate limiting adsorption step was chemisorption and adsorption rates were best described by the pseudo-second order model.